THE ROLE OF FINTECH COLLABORATION, REAL-TIME DATA ANALYSIS, AND ERP SYSTEMS IN IMPROVING BUDGET ACCURACY AND DECISION-MAKING QUALITY IN CORPORATE ACCOUNTING IN INDONESIA - Utami, Mega; Anggraeni, Reni; Barus, Irwan Irawadi (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study examines the role of fintech collaboration, real-time data analysis, and Enterprise Resource Planning (ERP) systems in enhancing budget accuracy and decision-making quality in corporate accounting in Indonesia. Employing a quantitative approach, data were collected from 150 accounting and finance professionals through a structured questionnaire using a 1–5 Likert scale. The data were analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results demonstrate that fintech collaboration, real-time data analysis, and ERP systems each have a positive and significant effect on budget accuracy. Furthermore, budget accuracy exerts a strong positive influence on decision-making quality and significantly mediates the relationship between the three technological constructs and decision-making quality. These findings suggest that the effective adoption of digital technologies enhances corporate financial management by strengthening budgeting processes, which in turn improves managerial decision-making. The study contributes to the literature on accounting and financial technology adoption and provides practical guidance for Indonesian corporations to optimize their budgeting and decision-making strategies in the digital era.